Monetary policy uncovered - Flying blind: The federal reserve's experiment with unobservables - Dimitri B. Papadimitriou; L. Randall Wray (Levy Economics Institute of Bard College, 1994)
Experience with a variety of targets has cast doubt on the likelihood that a single variable can be found to be closely and reliably linked to future inflation; it is even less likely that such a variable, should it be found, would somehow be under the control and manipulation of the Federal Reserve. This brief provides a review of the experiments with various targets undertaken by former Fed Chairman Paul Volcker and current Chairman Alan Greenspan. The authors contend that there is no reason to suppose that the Fed will discover a target variable whose control will yield stable prices. Finally, they conclude that economists lack sufficient information to calculate the costs of achieving stable prices in terms of unemployment and lost output.
Keywords: 330